Structural and Functional Changes in the Coupling of Fascial Tissue, Skeletal Muscle, and Nerves During Aging - Zullo, Alberto; Fleckenstein, Johannes; Schleip, Robert; Hoppe, Kerstin; Wearing, Scott; Klingler, Werner (Frontiers in Physiology, 2020)
Aging is a one-way process associated with profound structural and functional changes in the organism. Indeed, the neuromuscular system undergoes a wide remodeling which involves muscles, fascia, and the central and peripheral nervous systems. As a result, intrinsic features of tissues, as well as their functional and structural coupling are affected and a decline in the overall physical performance occurs. In this review, we summarize the evidence about the effect of aging on skeletal muscle, fascial tissue, and nerve system. In particular, we address the structural and functional changes occurring within and between these tissues and revise the effect of inflammation in aging. Furthermore, from the clinical perspective, we describe some approaches for the study and the treatment of age-associated modifications in the neuromuscular system, such as imaging and ultrasound-based methods, as well as tissue manipulation techniques.